Reforming Learning and Teaching in Asia-Pacific Universities Influences of Globalised Processes in Japan, Hong Kong and Australia - Ng, Chi-hung Clarence; Fox, Robert; Nakano, Michiko (Education in the Asia-Pacific Region: Issues, Concerns and Prospects, 2016)
This book focuses on learning and teaching as the core business of higher education and explores reformative efforts in response to the influences of globalised processes in three advanced economies in the Asia-Pacific region: Japan, Hong Kong and Australia. This is a significant book as it adds to limited discussions on the globalisation of learning debates, and scholarly reflections on the links between globalised processes and changing educational practices, critical to understanding the current challenges and options available for charting future development for universities in the Asia-Pacific region and beyond. It rejects an essentialising perspective that considers changes as inevitable and uniform. Instead it considers negotiations, arguments, and even resistance as competing forces and integral components of the process of reforming pedagogical practices in Asia-Pacific universities. This book discusses globalised processes as a new context for reforming learning and teaching and its focused discussions cover topics including meeting the needs of new student groups, new technological practices for change, use of English as an international language, and challenges in assessment and quality assurance.